Isolation of circulating tumor cells by a magnesium-embedded filter. (21st September 2015) - Liu, Yang; Xu, Tong; Xu, Yucheng; Kang, Dongyang; Xu, Lei; Park, Jungwook; Chang, Jay Han-Chieh; Zhang, Xiaoxiao; Goldkorn, Amir; Tai, Yu-Chong
Abstract: Circulating tumor cells (CTCs) are rare cancer cells that are shed by tumors into the bloodstream and that can be valuable biomarkers for various types of cancers. However, CTCs captured on the filter could not be released easily using the existing CTC analysis platforms based on size. To address this limitation, we have developed a novel magnesium (Mg)-embedded cell filter for capture, release and isolation of CTCs. The CTC-filter consists of a thin Ebeam-deposited Mg layer embedded between two parylene-C (PA-C) layers with designed slots for filtration and CTC capture. Thin Mg film has proved highly biocompatible and can be etched in saline, PBS and Dulbecco's modified eagle medium (DMEM) etc, properties that are of great benefit to help dissociate the filter and thus release the cells. The finite element method (FEM) analysis was performed on the Mg etching process in DMEM for the structure design. After the filtration process, the filter was submerged in DMEM to facilitate Mg etching. The top PA-C filter pieces break apart from the bottom after Mg completely dissolves, enabling captured CTCs to detach. The released CTC can be easily aspirated into a micropipette for further analysis. Thus, the Mg-embedded cell filter provides a new and effective approach for CTCs isolation from the filter, making this a promising new strategy for cancer detection.